Congenital cardiac anomalies detected in fetal autopsies: a case series - Srinivas, Swathi; K., Bharath Vignesh R.; Nagarajan, Priyathersini; Kalaivanan, Chitra; Joseph, Leena Dennis (International Journal of Contemporary Pediatrics, 2025)
Congenital cardiac anomalies are among the most common structural malformations of the developing fetus and account for a high percentage of fetal morbidity and mortality. Timely detection and comprehensive assessment are important in prenatal care, allowing for appropriate parental counseling and directing possible therapeutic interventions. Although significant advances in prenatal imaging modalities, especially fetal echocardiography and ultrasonography, have increased the rate of antenatal detection, some of these anomalies are only diagnosed during post-mortem examinations. Fetal autopsy continues to be a useful means of validating prenatal diagnoses and revealing unsuspected anomalies, particularly in the setting of intrauterine fetal loss or pregnancy interruption after the detection of fetal abnormalities. The anatomical information obtained from fetal autopsy is essential in the comprehension of congenital cardiac malformations, their related anomalies, and the possible genetic and environmental determinants of their development. This paper is a collection of congenital cardiac defects identified at fetal autopsy and the very significant role of post-mortem examinations in improving diagnostic sensitivity and affecting future clinical management.